Mitigating effects on target and by-catch species fished by drifting longlines using circle hooks in the South Adriatic Sea (Central Mediterranean) - Carbonara, Pierluigi; Prato, Giulia; Niedermüller, Simone; Alfonso, Sébastien; Neglia, Cosmidano; Donnaloia, Marilena; Lembo, Giuseppe; Spedicato, Maria Teresa (Frontiers in Marine Science, 2023)
Introduction Longline fishing gear has a higher by-catch rate than any other type of commercial fishing gear. Nowadays, there is an urgent need to find efficient management strategies to mitigate by-catch and the use of new hook types could be one of them. This study investigates the effects of a longline fishery (which targets swordfish, Xiphias gladius, in the South Adriatic Sea) replacing the traditional J-type hook with a circle hook (C-type hook) on target and by-catch species. Methods For this purpose, a fishing trip of nine days – with seven fishing sets – was monitored. For both targeted swordfish and by-catch specimens caught (i.e., blue shark, Prionace glauca; pelagic stingray, Pteroplatytrygon violacea; and loggerhead turtle, Caretta caretta), data about the hook type used (J-type vs. C-type), the specimen size, and their capture condition were collected. Results and discussion With all species, we observed no significant difference in catch-per-unit-effort (CPUE) or specimen lengths between the two hook types. In addition, the hook type did not significantly affect the capture condition of swordfish, pelagic stingray, or loggerhead turtle specimens; however, it significantly affected the capture condition of blue sharks. The percentage of blue shark specimens found in healthy condition was higher when using a C-type hook (71.5%) than when using a J-type hook (22.6%). Overall, these preliminary results suggest that the use of a C-type hook improves the condition of by-caught blue sharks without affecting the CPUE or size of the target species. In conclusion, the use of a C-type hook could reduce the detrimental effects of by-catch on some species in the Adriatic Sea; however, this finding needs to be confirmed by a study with a larger sample size.